The fifth UK paediatric diabetes services survey: meeting guidelines and recommendations?. Issue 10 (6th July 2010) - Gosden, Charlotte; Edge, Julie A; Holt, Richard I G; James, June; Turner, Bridget; Winocour, Peter; Walton, Chris; Nagi, Dinesh; Williams, Rhys; Matyka, Krystyna
Abstract : Aim: To assess the provision of UK paediatric and adolescent diabetes services and examine changes in service delivery since 2002. Method: Questionnaires were sent to the lead paediatric consultant from all paediatric and adolescent diabetes services (n=205). Questions were based on National Institute for Health and Clinical Excellence and Scottish Intercollegiate Guidelines recommendations for diabetes care in childhood. Results were analysed using parametric and non-parametric tests. Results: 129 Services (63%) returned questionnaires involving 220 clinics. Staffing has improved and 98% of consultants have a special interest in diabetes (89%, 2002). In 88% of services, the diabetes specialist nurse worked solely in paediatric diabetes (53%, 2002). Only 21% of clinics have a psychological professional integrated within the diabetes team (20%, 2002). Over 94% of services offered support with intensive insulin regimens causing problems at school for 36% of services. Almost all services offer annual microvascular screening (98–100%) but transitional care was variable; only 76% of services have specific local protocols for transition and 21% organise transfer by letter only. Conclusion: Paediatric and adolescent diabetes services are rising to the challenge of providing high-quality care despite rising prevalence and increasingly complex insulin regimes. Services have improved in a number of key areas but serious deficiencies remain.